2020
DOI: 10.3892/ol.2020.11815
|View full text |Cite
|
Sign up to set email alerts
|

High expression of endothelial progenitor cell‑induced angiogenic markers is associated with bile acid levels in HCC

Abstract: Endothelial progenitor cell (EPC)-induced angiogenesis activity is enhanced in hepatocellular carcinoma (HCC); however, the contributing factors remain unknown. The present study aimed to investigate the factors influencing the number of EPCs and circulating progenitor cells (CPCs), as well as the expression levels of vascular endothelial growth factor receptor 2 (VEGFR-2) and CD34, in patients with HCC. The expression levels of VEGFR-2 and CD34 were assessed in 72 HCC tumor and matched adjacent tissue microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In the late 19th century, some scholars have discovered the anti-angiogenic activity of UDCA and its derivatives, suggesting the potential of BAs for the treatment of diseases that are accompanied by uncontrolled angiogenesis, including tumors (39). In contrast, a subsequent study on liver cancer found that BAs levels were positively correlated with the expression levels of VEGFR-2 and CD34, that is, BAs promoted tumor angiogenesis in liver cancer (35). Coincidentally, another study showed that CDCA promotes esophageal cancer angiogenesis and tumor growth via the COX-2 pathway (36).…”
Section: Bile Acids In Cancer Angiogenesismentioning
confidence: 99%
“…In the late 19th century, some scholars have discovered the anti-angiogenic activity of UDCA and its derivatives, suggesting the potential of BAs for the treatment of diseases that are accompanied by uncontrolled angiogenesis, including tumors (39). In contrast, a subsequent study on liver cancer found that BAs levels were positively correlated with the expression levels of VEGFR-2 and CD34, that is, BAs promoted tumor angiogenesis in liver cancer (35). Coincidentally, another study showed that CDCA promotes esophageal cancer angiogenesis and tumor growth via the COX-2 pathway (36).…”
Section: Bile Acids In Cancer Angiogenesismentioning
confidence: 99%
“…In addition, several chemical drugs (such as The FXR Agonist Obeticholic Acid and Bushen Jianpi) can inhibit liver tumor metastasis in orthotopic mouse xenograft model and reduce the recurrence and metastasis rate of HCC patients by interfering with BAs levels (Table 1) (56, 57). Although information is limited, BAs also play a role in promoting HCC angiogenesis to a certain extent, that provides good conditions for tumor metastasis (59). In summary, BAs drive the progression of liver tumor metastasis in an indirect way, and antagonizing excessive BAs may provide an effective means of treating liver cancer.…”
Section: Bas Contribute To Hcc Metastasismentioning
confidence: 99%
“…The binding with membrane receptors promotes systemic effects of BAs, regulation of digestion and lipid metabolism, and differentiation of endothelial cells [49,50]. Moreover, there is evidence that the activation of BAs' membrane receptors promotes malignant transformation and cancer progression [51][52][53].…”
Section: Signaling Pathwaysmentioning
confidence: 99%